SEMIOTIC ANALYSIS OF THE REPRESENTATION OF CORRUPTION IN THE SHORT FILM PIRATES OF TEN THOUSAND BY FICTIVE STUDIOS - Suci Shinta Lestari; Cesy Cesy; Fenny Anita (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Corruption is a social issue that can be depicted through various media, including short films. The film Pirates of Sepuluh Ribuan by Fiktive Studios features various scenes that portray acts of corruption in a simple form through a children’s adventure story. This study aims to examine how corruption is represented in the short film Pirates of Sepuluh Ribuan. The study employs a descriptive qualitative approach using Roland Barthes’s semiotic analysis method. The research subjects are ten scenes from the film Pirates of Sepuluh Ribuan, analyzed across three levels of meaning: denotation, connotation, and myth. Data collection was conducted through observation of scenes, dialogue, and visual symbols in the film, which were then analyzed descriptively based on Roland Barthes’s concept of the sign. The results indicate that the film Pirates of Sepuluh Ribuan represents corruption through acts of manipulation, abuse of trust, trading of positions, misuse of facilities, abuse of authority, and violations of rules. On the denotative level, the film depicts children’s play activities with a pirate theme. On the connotative level, these activities represent deviant practices in social life. On the mythical level, the film establishes the understanding that corruption can stem from small acts that have become normalized in everyday life. The conclusion of this study indicates that the short film Pirates of Sepuluh Ribuan represents corruption as a form of manipulation, breach of trust, the buying and selling of positions, abuse of power, and the justification for a violation in the interest of certain purposes.